“Let us heed the voice of youth”: Laundry Detergents, Phosphates and the Emergence of the Environmental Movement in Ontario - Read, Jennifer (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1996)
AbstractThis paper uses the 1960s detergent debate to examine the shift to environmental attitudes in Ontario. The first phase of the detergent issue began in 1963 and addressed excessive foaming in the province's water created by detergent residues. The Ontario Water Resources Commission ignored protest from municipal governments and allowed the manufacturers to resolve the problem on their own. In 1969, the environmental phase of the issue began when phosphate-based detergents were blamed for the dwindling quality of Great Lakes water. The appearance of strong advocacy groups, especially Pollution Probe from the University of Toronto, marked this stage. Pollution Probe used science and strong media relations to mobilise public support to ban phosphate-based detergents. The paper assesses the success of strategies employed during both phases of the debate and ties that to the emergence of environmental attitudes among the public.